2009
DOI: 10.1074/jbc.m807477200
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger Receptor Collectin Placenta 1 (CL-P1) Predominantly Mediates Zymosan Phagocytosis by Human Vascular Endothelial Cells

Abstract: Collectin placenta 1 (CL-P1), a recently discovered scavenger receptor, mediates the uptake of oxidized low density lipoprotein and microbes. In this study, we investigated CL-P1-mediated binding and ingestion of yeast-derived zymosan bioparticles using Chinese hamster ovary (CHO) cells stably expressing human CL-P1 (CHO/CL-P1) and human vascular endothelial cells constitutively expressed CL-P1. The uptake of zymosan by CHO/CL-P1 was dependent upon the level of CL-P1 expressed on the membrane and was inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 36 publications
(28 reference statements)
1
50
0
Order By: Relevance
“…this multifunction in pathogen recognition has been suspected to be abolished because of protein functional differentiation in arthropods. through pathogen recognition, Prrs further mediate in opsonic effect, benefiting pathogen cleaning, such as agglutination mediated by c-type lectins [2,26,27], antibacterial activity mediated by PGrP-sB1 [16] and sr-enhanced phagocytosis [8]. PtLGBP exhibited obvious agglutination activity against Gram-negative bacteria V. parahaemolyticus, V. alginolyticus, and e. coli; Gram-positive bacteria B. megaterium; and fungi s. cerevisiae.…”
Section: Discussionmentioning
confidence: 99%
“…this multifunction in pathogen recognition has been suspected to be abolished because of protein functional differentiation in arthropods. through pathogen recognition, Prrs further mediate in opsonic effect, benefiting pathogen cleaning, such as agglutination mediated by c-type lectins [2,26,27], antibacterial activity mediated by PGrP-sB1 [16] and sr-enhanced phagocytosis [8]. PtLGBP exhibited obvious agglutination activity against Gram-negative bacteria V. parahaemolyticus, V. alginolyticus, and e. coli; Gram-positive bacteria B. megaterium; and fungi s. cerevisiae.…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytosis and macropinocytosis are closely related processes (Swanson, 2008(Swanson, , 2014, however, the regulatory architecture of these processes are not fully understood (Bloomfield et al, 2015). These processes are triggered by the interaction between the particles and various kinds of receptors (Jang et al, 2009;Ramirez-Ortiz et al, 2013) As for CNTs, phagocytosis of SWCNTs by macrophages (Dong et al, 2013) and macropinocytosis of MWCNTs through macrophage receptor with collagenous structure (MARCO) (Hirano et al, 2012) have been reported, while the interaction of CNTs with scavenger receptors (ScRs), which are important for both phagocytosis and micropinocytosis, has also been reported (Wang et al, 2012). The surface modification, size, and shape of the CNTs or their agglomerates may affect their internalization pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Wortmannin, a phagocytosis inhibitor (12) or Genistein, an inhibitor of caveolae-dependent uptake (18,19), had no effect on the endocytosis of ligands for CL-P1 (Fig. 6A, B).…”
Section: The Tyrosine Motif Is Required For Internalization Of Oxldl mentioning
confidence: 99%
“…Monoclonal antibody to clathrin heavy chain, -adaptin, -adaptin, 2 (AP50) and dynamin-2 were purchased from BD Biosciences (San Jose, CA). Monoclonal and polyclonal antibodies to CL-P1 (10,12) were obtained using the recombinant carbohydrate recognition domain (CRD) of human CL-P1 in E. coli. Immunoaffinity purification of antibodies was used to purify antigen-specific antibodies from a preparation of polyclonal antibodies to CL-P1.…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation